PENGARUH RISIKO BISNIS, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PENGRAJIN MEBEL DI PASAR MEBEL BIBIS - TUTI EDIATI (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2015)
The purpose of this study was (1) to test and measure the effect of business risk, profitabilias level as measured by return on assets (ROA), and profitability level as measured by return on equity (ROE) of the capital structure in the furniture craftsman at furniture market Bibis Surakarta , (2) To determine the effect of interaction between business risk, ROA, ROE on the capital structure in the furniture craftsman at furniture masrket Bibis Surakarta. (3) To determine the most dominant influence on the capital structure in the furniture craftsman at furniture market Bibis Surakarta. The object of this research is in the furniture craftsman at furniture market Bibis Banjarsari Surakarta. In this study population were entrepreneurs furniture craftsman furniture industry region in Bibis Surakarta as many as 85 employers. The samples were taken as many as 20 employers with non-probability sampling method, number of samples taken by the researcher's own judgment. Then to mengnalisis data using multiple linear regression, t test F test and coefficient of determination. Research found that there are significant posotif between business risk to capital structure in the furniture craftsman at furniture market Bibis Surakarta. There is a negative and significant influence between profitabilias level as measured by return on assets (ROA), and profitability level as measured by return on equity (ROE) of the capital structure in the furniture craftsman at furniture market Bibis Surakarta. The most dominant factor of influence on the capital structure in the furniture craftsman at furniture market Bibis Surakarta is a business risk. Capital structure in the furniture craftsman at furniture market Bibis Surakarta city can be explained by risk factors and business profitability level as measured by return on assets (ROA), and profitabilias level as measured by return on equity (ROE) of 72.30% and the balance of 27.70% describe the influence of other variables outside this research.